Surgical treatment of hepatic abscess guided by intraoperative ultrasound - Rosati, Luis Fernando; Rosati, Ana Luiza; Rocha, Ana Paula de Carvalho Miranda Rosati (Brazilian Journal of Case Reports, 2023)
Pyogenic liver abscesses are one of the complications of acute cholecystitis. Its dissemination can occur hematogenous, through the hepatic artery or the portal vein, or through biliary dissemination, due to ascending cholangitis. The germs involved are Escherichia Coli, Klebsiela pneumoniae, Anaerobic Streptococci and Enterococci. The importance of a prompt diagnosis and treatment is based on the severity of the clinical picture and its complications, such as morbidity and mortality. The main risk factors are Diabetes, Hypertension, cholelithiasis and previous abdominal surgery. The purpose of this study is the evaluation of the case and discussion about the forms of treatment and the demonstration of the importance of using the Ultrasound for localization of deep intrahepatic collections.